2022
DOI: 10.1371/journal.pgen.1010093
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing human knockouts to validate GPR151 as a therapeutic target for reduction of body mass index

Abstract: Novel drug targets for sustained reduction in body mass index (BMI) are needed to curb the epidemic of obesity, which affects 650 million individuals worldwide and is a causal driver of cardiovascular and metabolic disease and mortality. Previous studies reported that the Arg95Ter nonsense variant of GPR151, an orphan G protein-coupled receptor, is associated with reduced BMI and reduced risk of Type 2 Diabetes (T2D). Here, we further investigate GPR151 with the Pakistan Genome Resource (PGR), which is one of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Recently, a rare nonsynonymous, presumed inactivating, mutation (p.Arg95Ter) in the gene encoding the orphan G-protein coupled receptor 151 (GPR151), a Gα o1 -linked GPCR, was associated with lower odds ratio for T2D, obesity and coronary artery disease 6 and with reduced body-mass index (BMI) [6][7][8] , although another recent study found no significant associations between putative loss-of-function (LOF) GPR151 variants and BMI, T2D, or other metabolic traits 9 .…”
mentioning
confidence: 99%
“…Recently, a rare nonsynonymous, presumed inactivating, mutation (p.Arg95Ter) in the gene encoding the orphan G-protein coupled receptor 151 (GPR151), a Gα o1 -linked GPCR, was associated with lower odds ratio for T2D, obesity and coronary artery disease 6 and with reduced body-mass index (BMI) [6][7][8] , although another recent study found no significant associations between putative loss-of-function (LOF) GPR151 variants and BMI, T2D, or other metabolic traits 9 .…”
mentioning
confidence: 99%